The influence of P5 sustainable lifestyle of TOGA cultivation on the dimensions and faith - Siti Hanifah; Siti Roudlotul Hikamah; Imam Bukhori Muslim (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This research aims to determine the influence of the Pancasila Student Profile Strengthening Project (P5) on sustainable lifestyle cultivation of Family Medicinal Plants (TOGA) on the dimensions of Faith, Piety to God Almighty, and Noble Character. The research approach is quantitative, the research type is quasi-experimental, the design is a one-group pre-test post-test design, and the sample was obtained through purposive sampling. This research will be conducted once a week from January to April 2025. The population in this study consisted of students from Junior High School 1 Panti, with a sample of 31 students from class VII B. The instrument used is an observation sheet adapted from the 2024 Ministry of Education and Culture P5 development guide. Data analysis was conducted using percentages and statistics with the assistance of SPSS v25. The results of the percentage test showed a pre-test score of 36.03% (below expectations) and a post-test score of 90.52% (exceeding expectations). Since the data from this study is not normally distributed, although homogeneous, the effect was therefore tested using the Wilcoxon test. The results of the Wilcoxon analysis yielded a value of 0.000 (sig < 0.05), indicating a significant effect. These results indicate that P5 activities cultivating medicinal plants can enhance the dimensions of Faith, Piety to God Almighty, and Noble Character, as well as a sense of responsibility for protecting the surrounding environment. These results indicate that cultivating TOGA is highly suitable as an alternative for empowering students' character in learning.